The immune modulation effects of gemcitabine plus cisplatin induction chemotherapy in nasopharyngeal carcinoma. (30th March 2022) - Li, Xiao‐Min; Zhang, Xiao‐Min; Li, Jun‐Yan; Jiang, Ning; Chen, Lei; Tang, Ling‐Long; Mao, Yan‐Ping; Li, Wen‐Fei; Zhou, Guan‐Qun; Li, Ying‐Qin; Liu, Na; Zhang, Yuan; et al.
Abstract: Background: Studies are trying to add immunotherapy to gemcitabine and cisplatin (GP) induction chemotherapy, the standard therapy, in nasopharyngeal carcinoma (NPC) patients with locoregionally advanced disease. However, how the immune system responds to GP remains unknown. Method: We examined the dynamic changes of circulating immune cells and plasma cytokines in NPC patients administered with GP. Result: After GP administration, immunosuppressive myeloid cells, including CD11b+CD14+ monocytes, CD33+ myeloid cells, CD33+CD11+ myeloid cells, total MDSCs (CD33+CD11+HLA‐DR−/low), monocytic MDSCs, and granulocytic MDSCs decreased significantly. The regulatory T cells and B cells, two important suppressive lymphocyte subpopulations, also decreased. On the other hand, the levels of CD3+ T cells, total B cells, central memory CD4+ T cells, and pro‐inflammatory cytokines (including Interleukin [IL]‐1β, IL‐6, IL‐2, IL‐5, and IL‐8) increased significantly after GP administration. Besides, GP chemotherapy did not weaken the cytotoxic activity and proliferative capacity of T cells. Conclusion: Our results showed the immune modulation effect of GP induction chemotherapy in locoregionally advanced NPC, providing a solid basis for its combination with immunotherapy. Abstract : Through monitoring the dynamic changes in the peripheral immune cell populations and cytokines, we demonstrated that GP chemotherapy not only significantly decreased the immunosuppressive cells but also improved the T cell immunity in NPC patients. Our study provided a new insight into the anti‐tumor mechanism of gemcitabine and cisplatin chemotherapy. Furthermore, our findings offered solid basis for the combination of GP induction chemotherapy with immunotherapy in future studies.